Metastatic MHC class I-negative mouse cells derived by transformation with human papillomavirus type 16 - Šmahel, M (Nature Publishing Group, 2001)
In the endeavour to develop a model for studying gene therapy of cancers associated with human papillomaviruses (HPVs), mouse cells were transformed with the HPV type 16 (HPV16) and activated H-ras oncogenes. This was done by contransfection of plasmid p16HHMo, carrying the HPV16 E6/E7 oncogenes, and plasmid pEJ6.6, carrying the gene coding for human H-ras oncoprotein activated by G12V mutation, into secondary C57BL/6 mouse kidney cells. An oncogenic cell line, designated MK16/1/IIIABC, was derived. The epithelial origin of the cells was confirmed by their expression of cytokeratins. No MHC class I and class II molecules were detected on the surface of MK16/1/IIIABC cells. Spontaneous metastases were observed in lymphatic nodes and lungs after prolonged growth of MK16/1/IIIABC-induced subcutaneous tumours. Lethally irradiated MK16/1/IIIABC cells induced protection against challenge with 10(5)homologous cells, but not against a higher cell dose (5 × 10(5)). Plasmids p16HHMo and pEJ6.6 were also used for preventive immunization of mice. In comparison with a control group injected with pBR322, they exhibited moderate protection, in terms of prolonged survival, against MK16/1/IIIABC challenge (P< 0.03). These data suggest that MK16/1/IIIABC cells may serve as a model for studying immune reactions against HPV16-associated human tumours. © 2001 Cancer Research Campaign http://www.bjcancer.com